Jenis Produk Perawatan Rambut yang Digunakan untuk Meningkatkan Kepuasan Pelanggan di Salon - Laksita Leilani Indra Lukman; Alfina Aprilia; Olivia Zahra Ramadhani . YS; Sri Endah Wahyuningsih (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This research is motivated by the increasing demand for more personalized salon services by customers, particularly in selecting hair care products tailored to individual conditions and needs. This study aims to identify the types of hair care products used in salons and analyze their contribution to customer satisfaction. The method used was a systematic literature review (SLR) of various relevant scientific publications from 2016 to 2025. Data were collected through searching and selecting articles based on predetermined inclusion and exclusion criteria, then analyzed using thematic analysis to identify key patterns and themes. The results indicate that the use of hair care products significantly influences salon customer satisfaction. The level of satisfaction is influenced by the suitability of the product to the hair condition, the quality of the ingredients used, the effectiveness of the treatment results, and the competence of the therapist in applying the product. In addition to functional aspects, a positive service experience also strengthens customer perceptions of the quality of the treatment received. These findings confirm that hair care products are a strategic component of salon service quality and play a crucial role in building customer satisfaction and loyalty. Therefore, selecting appropriate and adaptive products needs to be a primary concern for salon managers to continuously improve service competitiveness.